PROBLEMS OF THE ARAL RIVER AND METHODS OF IMPROVEMENT OF WATER ECOLOGICAL RESOURCES OF UZBEKISTAN - Ishonkulova K. Q.; Ismatullaeva Z. I.; Xalilova F. A. (European Science Publishing, 2024)
The Aral Sea basin is a region of increased attention of the world community and an arena of international cooperation in resolving the Aral crisis. The environmental situation in the region, associated with the drying up of the Aral Sea, is a problem of international importance, and its preservation and sustainable development are of paramount importance both at the global and regional levels.
Keywords: Aral problems, ecology, Environmental Protection.